Anmeldelser - Pedersen, Peder Kaj (Danish Yearbook of Musicology, 2016)
Review of: Michael Fjeldsøe: Kulturradikalismens musik. Copenhagen: Museum Tusculanum Press, 2013. Danish Humanist Texts and Studies, 45.